2008
DOI: 10.1111/j.1937-8327.2003.tb00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Consequences of Coaching Behavior

Abstract: Proponents of the learning organization acknowledge that leaders and managers must assume roles as coaches in organizations that aspire to become learning organizations. The concept of the manager as coach is becoming increasingly popular as a way to facilitate learning and improve employee performance. Yet, despite the research that has been done on coaching, studies generally focus on characteristics of good coaches, requisite coaching skills, and employees' perceptions of the improvement in managers' coachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 22 publications
(40 reference statements)
1
38
0
1
Order By: Relevance
“…In the present study, three types of work situations were found to precipitate participation in informal learning: new teaching tasks, new leadership roles, and adherence to policies and procedures. These findings corroborate, in part, previous studies that found new work assignments to be important triggers to informal learning (Ellinger, 1999).…”
Section: Theoretical Perspectives On Triggers To Participation In Infsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, three types of work situations were found to precipitate participation in informal learning: new teaching tasks, new leadership roles, and adherence to policies and procedures. These findings corroborate, in part, previous studies that found new work assignments to be important triggers to informal learning (Ellinger, 1999).…”
Section: Theoretical Perspectives On Triggers To Participation In Infsupporting
confidence: 90%
“…While previous studies of informal learning have focused predominantly on the identification of knowledge and skills that individuals seek to obtain through informal learning and the types of learning activities in which they engage (Daley, 1997;Kozlowski, 1995;Lohman, 2000), two relatively unexamined areas of investigation concern the types of work situations that trigger participation in informal learning activities and the types of personal characteristics that enhance a person's motivation to engage in such activities (Ellinger, 1999). Greater understanding of these aspects of informal learning could provide insights for reconsidering the design of workplace learning initiatives and the design of work environments, with the ultimate goal of helping professionals deal with challenging work situations in a timely and effective manner.…”
Section: Margaret C Lohman Penn State Harrisburgmentioning
confidence: 99%
“…Mumford, 1993;Bevan and Hayday, 1994;Heraty and Morley, 1995;de Jong et al, 1999;Ellinger, 2003). However, until very recently, there has been limited research into what managers do as facilitators of learning (Mumford, 1993;Horowitz, 1999).…”
Section: Introductionmentioning
confidence: 93%
“…Although there is an extensive literature on developmental roles that managers may play, such as mentor and coach, much of this literature is prescriptive and rhetorical, and there appear to be relatively few examples of substantive research and empirical studies focusing on managerial behaviours (Horowitz, 1999;Ellinger, 2003;Ellinger et al, 2005), although MacNeil (2003) has undertaken interesting work exploring the roles of supervisors as facilitators of learning. Horowitz acknowledges that the notion of line managers having responsibility for development is valid; however, he concludes that the 'HRD literature and practice fails to address satisfactorily how this should occur' (Horowitz, 1999, pp.…”
Section: Introductionmentioning
confidence: 97%
“…Scholars identified a number of variables that promote managerial use of coaching (Anderson, ; Gilley, Gilley, & Kouider, ; Turner & McCarthy, ) and realized that developing the required skills takes time as well as a deliberate process (Grant, ; Grant & Hartley, ). Other antecedents that facilitate the use of coaching on organizational behaviors are the organization's focus on long‐ or short‐term goals (Pousa & Mathieu, ), organizational climate (A. E. Ellinger, Ellinger, & Keller, ), and the existence of gaps and learning opportunities (A. D. Ellinger, ).…”
Section: Literature Reviewmentioning
confidence: 99%